Ice Force Measurements on a Bridge Pier in the St. Regis River, New York - Haynes, F. D.; Sodhi, Devinder S.; Zabilansky, Leonard J.; Clark, Charles H. (1991)
An ice force panel was installed on the upstream nose of a pier of the new (1989) bridge over the St. Regis River at Hogansburg, New York. This panel is a simply supported beam, pinned at the bottom, and has a load cell for the reaction at the top. Ice forces measured with this panel during the 16 March 1990 ice run are presented. Ice failed against the panel by impact, by crushing and possibly by splitting of the floes. Bridge, Ice, River ice, Bridge pier, Ice forces, St. Regis River, Design code, River.